Reception of Francis Hutcheson’s Views in Immanuel Kant’s Philosophy of the Power of Judgment - Śliwa, Marta (Studia Warmińskie, 2021)
The following dissertation aims at presenting the dependencies between the aesthetic theory by the Scottish philosopher Francis Hutcheson and the critic philosophy by Immanuel Kant. Those issues seem to be worth discussing in the light of some new research into the British aesthetics: particularly, for its significance in the field of newly created domain that aesthetic has become after Alexander Baumgarten and, mostly, after critical philosophy by Immanuel Kant. The comparison of the views held by Hutcheson and Kant shows the importance of the theory of beauty presented by the Scottish philosopher that results not only from his acknowledging the epistemological significance of an aesthetic experience and accepting that it is conditioned by disinterestedness of perception. What is important is Hutcheson’s place in the evolution of the concept of aesthetics, which took place in the 18th century and which was crowned by Kant and his Critique of the Power of Judgment.